Exploring factors influencing the adoption of smart elderly care products: An enhanced UTAUT model analysis of smart wearables - Qin, Huibo; Li, Quanlin (Edelweiss Applied Science and Technology, 2024)
This study investigates factors influencing elderly adoption of smart wearables. Using a modified Unified Theory of Acceptance and Use of Technology (UTAUT), it surveyed 395 elders. Structural equation modeling (SEM) analysis reveals positive impacts of facilitation, performance, and social influence on adoption, while cost and risk hinder it. Adoption intention mediates usage. The study emphasizes usability, functionality, social acceptance, and affordability in designing and marketing smart wearables for the elderly, aiming for broader acceptance and usage.